2016
DOI: 10.1002/ar.23324
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Examination of an Assemblage of Psittacosaurus (Dinosauria: Ceratopsia) Juveniles From the Yixian Formation (Liaoning, China)

Abstract: Psittacosaurus is one of the most abundant dinosaurs known, which allows for extensive study of its growth and form. Previous studies have evaluated growth trajectories of Psittacosaurus using bone histology. However, we present the first study of Psittacosaurus comparative juvenile histology and describe the histology of Psittacosaurus within its first year of life based on multiple sections taken from an exquisite monospecific assemblage of juveniles from the Yixian Formation in Liaoning, China. Specimens st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Zhao et al . () further demonstrated that juvenile Psittacosaurus grew extremely quickly and had a combination of radial and reticular canals in the first year of life. A single specimen of Cerasinops has been histologically examined, MOR 300, which was likely sexually mature at its time of death (Chinnery and Horner, ).…”
Section: Discussionmentioning
confidence: 89%
“…Zhao et al . () further demonstrated that juvenile Psittacosaurus grew extremely quickly and had a combination of radial and reticular canals in the first year of life. A single specimen of Cerasinops has been histologically examined, MOR 300, which was likely sexually mature at its time of death (Chinnery and Horner, ).…”
Section: Discussionmentioning
confidence: 89%
“…2007; Bo et al . 2016). The abundance and quality of the specimens reflect the conditions of their entombment, overwhelmed by falling volcanic ash (Zhao et al .…”
Section: Figmentioning
confidence: 99%
“…Additionally, palaeohistological analyses have enabled estimation of the age of individuals within a dinosaur assemblage, leading to inferences about the population structure and reconstruction of the population ecology for some dinosaur taxa (e.g. Erickson, Makovicky et al, 2009;Woodward et al, 2015;Bo et al, 2016). Determining the age of individual dinosaurs through palaeohistological assessments has also helped to sort out dinosaur taxonomy when ontogenetic variation may complicate species identification (e.g.…”
Section: Introductionmentioning
confidence: 99%